Characterization by Electrical Impedance of an In Vitro Model Based on Tumor Cell Spheroids - Perisé-Badía, Ismael; López-Alonso, Borja; Briz, Pablo; Lucía, Óscar; Sarnago, Héctor; Ochoa, Ignacio (Jornada de Jóvenes Investigadores del I3A, 2024)
The main objective of this work is to assess the loosening effect of blebbistatin, a specific inhibitor of myosin II activity, on glioblastoma spheroids. Electric impedance will be used to quantify the effect of this drug, with therapeutic potential for facilitating the access of other treatments into the tumor.